EFFECTS OF GLYCOSIDES BASED FENUGREEK SEED EXTRACT ON SERUM TESTOSTERONE LEVELS OF HEALTHY SEDENTARY MALE SUBJECTS: A EXPLORATORY DOUBLE BLIND, PLACEBO CONTROLLED, CROSSOVER STUDY - MOKASHI, MAHESH; SINGH-MOKASHI, RENU; MOHAN, VISHWARAMAN; THAKURDESAI, PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate acute effects of IND9 supplementation on serum testosterone levels in healthy sedentary male subjects. Methods: The study was designed as randomized, double blind, placebo controlled, two period, crossover study with 7 days of washout period using single study center. Sixteen healthy male subjects were randomized and received single dose of 600 mg (two capsules of 300 mg) of either IND9 or matching placebo capsules during each of the 2 study periods of 10 h each. Blood samples were collected three times at 3 h, 7 h and 10 h. The outcome measures were measurement of serum free testosterone (mFT) and total testosterone (TT), calculated levels of free testosterone (cFT), bioavailable testosterone (BT) levels and safety parameters. Results: During the study period, significant time-dependent interactions were found for mFT and cFT levels (within Placebo and IND9 supplemented arms), BT levels (within IND9 but not in Placebo arm) and TT levels (none of the arms). Two-way ANOVA of data of change from baseline at 10 h showed no significant interactions between the treatments and periods (absence of crossover effect) for all measures. Pairwise comparisons between change from baseline data (at 10 h) by unpaired ‘t' test showed significant increase in TT, BT and cFT but not in mFT levels in IND9 arm as compared to respective levels in placebo arm. The supplementation of IND9 and placebo was found to be safe and well-tolerated. All values were found within physiological limits. Conclusion: Acute administration of IND9 capsule supplementation to sedentary males showed potential androgenic benefits with good safety profile. Keywords: Fenugreek seed extract, serum testosterone, Bioavailable, healthy sedentary subjects